Community empowerment through research, innovation and Open Access : proceedings of the 3rd International Conference on Humanities and Social Sciences (ICHSS 2020), Malang, Indonesia, 28 October 2020 /: proceedings of the 3rd International Conference on Humanities and Social Sciences (ICHSS 2020), Malang, Indonesia, 28 October 2020. (2021) - Unknown
No abstract available